(untitled) (The Journal of Psychology and Sociology, 2024)
This article examines the relationship of self-esteem with perseverance, optimism, activity and responsibility. The authors analyzed the scientific literature in order to further explore self-esteem for its improvement. The relevance of this study is determined by the fact that self-esteem forms an idea of oneself, is an important regulator of behavior and affects all spheres of personal life. It determines the quality of life, efficiency and self-realization of the individual. The purpose of this study is to examine the features of self-esteem, the relationship with persistence and determine its socio-psychological factors. The study involved 200 students aged 18 to 23 years from six universities in Kazakhstan. Five diagnostic techniques were used: Rosenberg Self-Esteem Scale; Optimism and Activity Scale, AOS; Carver-White questionnaire, BIS/BAS; Locus of Control Survey (Rotter); Hexaco PI-R60 questionnaire. The results of the conducted research showed the relationship of self-esteem with such indicators as optimism and activity, sociability and responsibility. The influence on self-esteem of factors such as sports, self-belief, parental support, satisfaction with appearance and studies, academic performance, suicidal thoughts and loneliness. According to the empirical analysis, the tendency of respondents to overestimate their self-esteem was found. The paper discussed the characteristics of students their values and other indicators. The study showed that 23.5% of students feel lonely, almost the same number of students think about suicide. Thus, this study provides new knowledge about self-esteem and its relationship with other psychological factors. It contributed to the understanding of the role of self-esteem in the formation of self-image and personality behavior, and is also of practical value for the development of psychological programs and techniques for working with students’ self-esteem. Key words: self-esteem, self-confidence, optimism, activity, persistence.